Integrating information management for Microsoft Works and Works for Windows - Fairhurst, Maureen (South Melbourne, Vic. : Nelson, 1993)
Information needs and integrated systems. Business spreadsheets. Business databases. Manipulating data in a database. Moving and integrating data. Business graphics. Word processing and mail merge. Accessories and options. Developing an integrated business information system. Communications
Keywords: Computer; Microsoft Works; Microsoft Works for Windows; Microsoft Works for WindowsIntegrated software; Microsoft Word